Seroprevalence of hepatitis B and hepatitis C among blood donors in Sierra Leone: A multi-year retrospective study. (October 2020) - Tognon, Francesca; Sevalie, Stephen; Gassimu, Joseph; Sesay, John; Hann, Katrina; Sheku, Mohamed; Bearse, Emily; Di Gennaro, Francesco; Marotta, Claudia; Pellizzer, Giampietro; Putoto, Giovanni; Lado, Marta; et al.
Highlights: National prevalence of viral hepatitis in Sierra Leone is still unknown. Among almost 30, 000 blood donors from five blood banks across the country, HBV and HCV prevalence was overall 10.8% and 1.2% respectively. Over 80% of donations were family replacement. Infection was strongly associated with being a first-time donor. Blood donations continued uninterrupted throughout the Ebola outbreak. Abstract: Objectives: In Sierra Leone, very little data are available on hepatitis B virus (HBV) and hepatitis C virus (HCV) prevalence. Blood donor screening permits estimation of the prevalence of transfusion transmissible infections in a general open population. We analyzed blood donor data in Sierra Leone to estimate national viral hepatitis prevalence and identify risk factors for hepatitis infection among the donor population. Methods: We conducted a retrospective data analysis in five government hospitals. We collected HBV and HCV screening results, donor demographics, and donation type (family replacement or voluntary donor; first-time or repeat). Univariate and multivariate analyses were performed to determine associations between infections and socio-demographic factors. Results: The number of donors screened was 29, 713. The overall prevalence was: 10.8% (3200) for HBV and 1.2% (357) for HCV. HBV infection was most strongly associated with male sex ( p : <0.0001) and younger age ( p : <0.0004 for the 22–27 age group). Both HBV and HCV infection were higher in certain locations. Conclusion: Our findings stress the presence of viral hepatitis infection throughout the country and the need to invest in safe blood services, vaccination and treatment of viral hepatitis at the national level.